(untitled) (Jurnal Pembangunan Sosial, 2009)
This article examines how changes in family institutions especially the increasing of single parents, affect the future of the elderly in society. To date single parents amongst the Malay society in Malaysia can be considered as a social phenomena, whereas at the same time, the magnitude and the proportion of the elderly are increasing. Based on 500 samples amongst single parents in Kelantan, Terengganu and Pahang, this article shows that these single parents, dispite their main task to take care of their elderly members, they themselves are full of daily problems. This situation can influence the future of the elderly in society. Thus, this article suggests strong support for the creation of caring society in Malaysia.